Vivências de adolescentes anoréxicas - Ramos, Fabiana Neme Nogueira [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Abstracts: Anorexia is an eating disorder that brings serious injuries to the health, physical and emotional development of the sick one and can lead to death. With the incidence growing since half of the 20th century, anorexia is related to the modern occidental esthetics patterns, which gives more importance to skinny bodies and worships the body, being more common in teenagers and young women. The most found symptoms are eating restrictions, weight loss, gastrointestinal problems, amenorrhea, and others. A very present fact in the anorexic teens is the disturbed perception of themselves and their bodies, although there are few researches that reveal how these girls live and give meanings to their experiences. The main objective of this present work is to comprehend the anorexic girl's lives in a phenomenological way, trying to study the subjective phenomenon to contribute to understand what happens with those girls and find better therapy possibilities to help those patients. For the results, it was used semi structured interviews, audio recorded, with 9 adolescents of the female gender, between the ages of 16 and 22years old, which had diagnosed with the bulimic and the restrictive nervous anorexia disorder. The questions were based in how they saw their bodies, the family relationship (with the parents and siblings); the auto perception and the care with their bodies. The answers were analyzed with the living life as they related to the thematic category meanings given by the same girls to their experiences, according the studies objective. The main results found reveal a life of anxiety and anguish facing a body seen as fat, which doesn't show the reality. Those lives resulted in many wishing a skin and idealized body. The eating habits are seen an unpleasant, generating guilt, scare and pain, because of the simple thought of gaining weight. Health means being skinny, even if the have to starve... (Complete abstract click electronic access below)

A anorexia é um transtorno alimentar que traz graves prejuízos à saúde e ao desenvolvimento físico e emocional das pessoas doentes, além de poder levar à morte. Apresentando crescente incidência desde a segunda metade do século XX, a anorexia está relacionada às exigências estéticas ocidentais modernas que privilegiam a magreza e o culto ao corpo, sendo mais comum em mulheres jovens e adolescentes. Dentre os sintomas da anorexia encontram-se a restrição alimentar, perda de peso acentuada, problemas gastrintestinais, amenorréia, entre outros. Uma característica bastante presente entre as adolescentes anoréxicas é a percepção distorcida de si e de sua imagem corporal, no entanto, há poucas pesquisas na literatura que revelam como essas adolescentes vivenciam e dão significado às suas experiências. O presente trabalho teve por principal objetivo compreender a vivência de adolescentes anoréxicas numa abordagem fenomenológica, buscando abordar os aspectos subjetivos do fenômeno e, desta forma, contribuir para aprofundar sua compreensão e incrementar as possibilidades terapêuticas de pacientes com esta enfermidade. Foram realizadas entrevistas semi-estruturadas, gravadas em áudio, com nove adolescentes do sexo feminino, na faixa etária de 16 a 22 anos de idade, diagnosticadas com o transtorno de anorexia nervosa de tipo restritivo e bulímico. O roteiro de entrevista conteve questões disparadoras dos relatos, abordando a visão do corpo; as relações familiares (adolescente x mãe; adolescente x pai; adolescente x irmãos); a autopercepçao e os cuidados com o corpo. Após a coleta dos dados, as entrevistas foram transcritas para posterior análise destacando-se as vivências relatadas em categorias temáticas e sínteses compreensivas dos significados atribuídos pelas adolescentes à suas experiências, de acordo com os objetivos do estudo...
Keywords: Anorexia; Adolescência; Fenomenologia; Vivências; Anorexia; Phenomenological